2018
DOI: 10.1101/386458
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The crossover function of MutSγ is activated via Cdc7-dependent stabilization of Msh4

Abstract: The MutSγ complex, Msh4-Msh5, binds DNA joint-molecule (JM) intermediates during homologous recombination to promote crossing over and accurate chromosome segregation at the first division of meiosis. MutSγ facilitates the formation and biased resolution of crossoverspecific JM intermediates called double Holliday junctions. Here we show that these activities are governed by regulated proteasomal degradation. MutSγ is initially inactive for crossing over due to an N-terminal degron on Msh4 that renders it unst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 127 publications
(141 reference statements)
0
2
0
Order By: Relevance
“…However, the physical interaction observed between Zip4 and Msh5 suggests that these complexes, probably along with Mer3, act synergistically on DNA intermediates to promote stable SEI intermediate formation (Figure 3b-c). During this process, SEI will be progressively stabilized by the MutSγ heterodimer and the phosphorylation of Msh4 protein (He et al 2018). The physical link observed between Zip3 and the MutSγ complex suggests that Zip3 consolidates the mechanism of CO maturation by further stabilizing this complex (Agarwal and Roeder 2000) ( Figure 2b).…”
Section: Integrated Functions Of Zmm Proteins In Promoting and Coordimentioning
confidence: 99%
See 1 more Smart Citation
“…However, the physical interaction observed between Zip4 and Msh5 suggests that these complexes, probably along with Mer3, act synergistically on DNA intermediates to promote stable SEI intermediate formation (Figure 3b-c). During this process, SEI will be progressively stabilized by the MutSγ heterodimer and the phosphorylation of Msh4 protein (He et al 2018). The physical link observed between Zip3 and the MutSγ complex suggests that Zip3 consolidates the mechanism of CO maturation by further stabilizing this complex (Agarwal and Roeder 2000) ( Figure 2b).…”
Section: Integrated Functions Of Zmm Proteins In Promoting and Coordimentioning
confidence: 99%
“…In mice, it has been suggested that the balance of RNF212mediated SUMOylation and HEI10-mediated ubiquitylation determines the stability of MutSγ complex by protecting it from proteolysis at CO-specific DNA intermediates (Qiao et al 2014). Interestingly, a recent study in budding yeast indicates that another type of post-translational modification is important for MutSγ complex stability (He et al 2018).…”
Section: O the D-loop Binding Mer3 Helicasementioning
confidence: 99%